2023
DOI: 10.3390/rs15030763
|View full text |Cite
|
Sign up to set email alerts
|

A Google Earth Engine-Based Framework to Identify Patterns and Drivers of Mariculture Dynamics in an Intensive Aquaculture Bay in China

Abstract: Although mariculture contributes significantly to regional/local economic development, it also promotes environmental degradation. Therefore, it is essential to understand mariculture dynamics before taking adaptive measures to deal with it. In the present study, a framework that integrates the Google Earth Engine (GEE) based methods and GeoDetector software was developed to identify patterns and drivers of mariculture dynamics. This framework was then applied to Zhao’an Bay, which is an intensive aquaculture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Just over half of all studies used Machine Learning algorithms, with over 40% using Deep Learning approaches alone. With seven applications, Random Forest accounts for the majority of Traditional Machine Learning approaches [51,53,54,65,66,79,81], followed by Support Vector Machine [9,65] and Decision Tree [64,65] (two each) along with Fuzzy C-means [59] and K-means [81] (one each). This indicates that Random Forest plays a prominent role in recognition due to its flexibility and adaptability.…”
Section: Methods Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…Just over half of all studies used Machine Learning algorithms, with over 40% using Deep Learning approaches alone. With seven applications, Random Forest accounts for the majority of Traditional Machine Learning approaches [51,53,54,65,66,79,81], followed by Support Vector Machine [9,65] and Decision Tree [64,65] (two each) along with Fuzzy C-means [59] and K-means [81] (one each). This indicates that Random Forest plays a prominent role in recognition due to its flexibility and adaptability.…”
Section: Methods Usedmentioning
confidence: 99%
“…Raft aquaculture was the most studied (46%) [31,32,37,39,46,50,[55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] and 12% of aquaculture studies looked specifically at cages [40,52,[74][75][76][77]. The remaining 42% investigated different types of aquaculture including raft, cage or longline in combination [33][34][35][47][48][49]53,54,[78][79][80][81][82][83][84][85][86][87][88][8...…”
Section: Development Of Research Interest Over Timementioning
confidence: 99%
“…Xing et al [26] extracted the algae culture area by using the differential vegetation index and revealed that it has no inevitable relationship with the formation of green tide in the Yellow Sea by retrieving the spatiotemporal development process through remote sensing, which has great significance to guiding the spatial planning of mariculture and the prevention and control of green tides in the Yellow Sea. Wang et al [27] extracted the aquaculture sea area based on the GEE framework and random forest model and determined the dynamic pattern and driving factors of mariculture. However, the traditional index method and machine learning supervised classification method cannot escape the phenomena of "same spectral characteristics, different matter" and "same substance, different spectrum" and cannot automatically extract the original feature information.…”
Section: Related Workmentioning
confidence: 99%